Barthel Index: creation and validation of two cut-offs using the BRASS Index: Barthel index: cut-offs’creation using BRASS - Strini, Veronica; Piazzetta, Novella; Gallo, Andrea; Schiavolin, Roberta (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Hospital discharge should be planned during the first days of stay to avoid an inappropriate length of stay and an early rehospitalization. Blaylock Risk Assessment Screening Score Index (BRASS index) evaluates the risk of difficult discharge, Barthel Index the level of autonomy in “activities of daily living” (ADL). This is a prospective observational study, performed in Padua’s Hospital (Italy), with the purpose of validating two cut-offs in the Barthel Index using the BRASS Index, in order to find three bands for difficult discharges: low, medium and high risk. Methods: Two studies have been conducted: a pilot study in 2017 with 153 patients and a validation study in 2018 with 253 patients, in order to validate data emerged from the pilot study. Using a statistical method, two cut-offs have been identified in the Barthel Index. Results: Both of study showed that the grade of autonomy is correlated with the risk of difficult discharge. A Barthel score between 0 and 35 corresponds to a high risk, between 35 and 70 to a medium and over 75 to a low. Discussion: This study suggests that, by the use of only Barthel Index, it may be possible to identify patients who may have difficulty in early discharge. This result suggests that the degree of functional dependence is predictive of the risk of difficult discharge. Further studies are needed to confirm the correlation between these data also in other realities (e.g. outside hospital departments). Conclusion: Nurses could use a single instrument to evaluate the autonomy and the risk of difficult discharge in order to identify early patients that need a discharge plan. (www.actabiomedica.it)